APPLICATION OF IPTEKS BASED ON LOCAL FEED WASTE FOR LIVESTOCK FARMER GROUP IN TUNTUNGAN II VILLAGES , PANCURBATU, DELI SERDANG REGENCY - Sadeli, Achmad (Talenta Publisher Universitas Sumatera Utara, 2019)
Deli Serdang Regency is one of the regencies in North Sumatra which has the potential for developing beef cattle consists of cattle and goats. Livestock commodities such as beef cattle and goats have indirect linkages to input-output between industries, consumption and investment. The problem faced by farmers until now is the problem of livestock productivity that still cannot be optimized. In general, optimization of livestock productivity is closely related to aspects of breeding, feeding and management. The fundamental problems faced by partners today involve providing and feeding that meets the needs of livestock as well as fast and good fattening. The planned activities that will be carried out include: (1) Preparation of forage fermentation for animal feed, (2) Preparation of complete feed fermentation and (3) Preparation of Multi Nutrient Blocks (MNB). The details of the output of the program produced include: 1) Mastering fermentation-based agricultural and plantation waste processing technology 2) Extension services and assistance to increase productivity of beef cattle 3) Independence of farmers in processing cassava chips industrial waste as animal feed to improve their quality and availability in the form of products fermented feed and complete feed 4) Mastering livestock supplement making technology in the form of Multi Nutrien Block (MNB) 5) Guidebooks, leaflets, seminars and scientific publications. The result of this service, farmers can make fermented feed, complete feed and multi nutrient blocks (MNB) well. The conclusion of this service needs further service by utilizing other local food waste sources so that farmers have more choices of feed given to their livestock.